BUDIDAYA SAYUR SECARA HIDROPONIK DAN IKAN LELE (MIX FARMING) DALAM MEMPERTAHANKAN KETAHANAN PANGAN KELUARGA DI DESA JATIWARINGAN MAUK TANGERANG - Saleh, Khaerul (Jurnal Pengabdian Dinamika, 2021)
Jatiwaringin Village, Mauk, Tangerang Regency is a village located in the north of Tangarang Regency or often known as Pantura Tangeranga, with land in the form of rice fields and rainfed moor. As a result of the Covid-19 pandemic, several food crop commodities have experienced a decline, coupled with government policies related to social restrictions (PSBB and PPKM). To deal with this condition, one alternative solution is to use the yard and yard of the house as land for plant cultivation through a mix farming program. A structured and solid institution both locally and nationally is the PKK, the involvement of the PKK in running the food program, especially Pokja 3 and 4, is very important in accordance with its role and function. To deal with these conditions, one alternative solution is to use the yard and yard for plant cultivation, but due to the limited knowledge and skills possessed and the relatively high patriarchal culture, the existing yard land is left unmanaged. Increased knowledge, insight and skills of the people of Jatiwaringan Village in managing yard land for plant cultivation where the PKK Group is one of the pioneers. To achieve the output targets according to the objectives, community service activities are carried out through several stages ranging from coordination and socialization to the community, implementation in the field, to monitoring and evaluation. The community service program carried out in conjunction with the thematic Student Work Kuyliah (KKM) activity in 2021 has been going well. This program was attended by administrators and PKK members, and supported by the RT Chair and Jatiwaringan Village Head. The results of the service show that the participation of the Jatiwaringin community in activities is high, the community is more skilled and very enthusiastic in managing the yard and is expected to provide broad benefits by being able to provide some food from the crops in the yard, especially during the Covid-19 pandemic.